URAPIDIL: MODERN MEDICINE FOR THE TREATMENT OF HYPERTENSIVE CRISES - A. V. Melekhov; Yu. I. Ostrovskaya (Столичная издательская компания, 2015)
Aim. To study the antihypertensive efficacy of urapidil, as well as to determine the optimal target level of systolic blood pressure (BP) in patients with hypertensive crisis complicated by a hemorrhagic stroke. Material and methods. Patients (n=86) aged 46-87 years (42 men and 44 women) who were admitted to hospital with hypertensive crisis complicated by a hemorrhagic stroke were included into the study. Patients were randomized into two groups: standard treatment (n=20) or urapidil treatment (n=66). The efficacy of treatment was assessed by clinical data, BP and heart rate dynamics. Patient survival was also assessed. Results. Mortality in urapidil group was 33% vs 70% in standard therapy group. Systolic BP in urapidil group decreased from 208 (203-222) mm Hg to 159 (149-180) and to 145 (141-153) mm Hg after 20 and 220 minutes, respectively, (p<0.001 for both), and diastolic BP from 108 (102-119) mm Hg to 90 (82-97) and 82 (80-90) mm Hg, re- spectively. Significant BP dynamics was also observed in standard therapy group. The target systolic BP level of 136-147 mm Hg was associated with better patient survival. Conclusion. The patients in urapidil group reached the target BP by the 20-th minute from the start of treatment, and this was accompanied by a better survival.